TRADITIONAL VS. MODERN EDUCATION SYSTEMS - Ko`shkinova Aynash Garifulla Qizi; Khamitov Eldorbek Erkinovich (TADQIQOTLAR, 2026)
ABSTRACT: The comparison between traditional and modern education systems remains a central issue in contemporary educational research. As societies evolve and the demands placed on learners increase, education systems must adapt to prepare students for academic, professional, and social challenges. This article provides a comprehensive comparison of traditional and modern education systems by examining their philosophical foundations, teaching methods, roles of teachers and learners, and overall impact on learning outcomes. Based on an analytical review of academic literature, the study highlights the strengths and limitations of both systems and argues that an integrated approach may offer the most effective solution for improving educational quality in the modern world.